2022
DOI: 10.1111/jvim.16365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resting cortisol concentration testing in dogs with chronic gastrointestinal signs

Abstract: Background Resting cortisol concentrations are routinely measured in dogs with chronic gastrointestinal signs to rule out hypoadrenocorticism based on a concentration >2 μg/dL (>55 nmol/L). Hypothesis/Objectives To assess the cross‐sectional prevalence of hypoadrenocorticism in a group of dogs with chronic gastrointestinal signs presented to a referral internal medicine service. Animals Two‐hundred and eighty‐two client‐owned dogs with chronic gastrointestinal signs and with resting cortisol concentration test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…In this multicenter prospective study, the prevalence of EEH in a cohort of dogs with CGD presented to 2 referral institutions was 0.9% (95% CI, 0.1%‐4.8%). The estimated prevalence in the present study closely corresponded with the overall prevalence of HA in the general canine population (between 0.06% and 1.1%), 1,22‐24 and with that recently reported in a large group of dogs with signs of CGD 16 . However, the results of this study demonstrated a lower prevalence of EEH than previously described in dogs with signs of CGD presented to several referral centers in Germany and in the Netherlands 15 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this multicenter prospective study, the prevalence of EEH in a cohort of dogs with CGD presented to 2 referral institutions was 0.9% (95% CI, 0.1%‐4.8%). The estimated prevalence in the present study closely corresponded with the overall prevalence of HA in the general canine population (between 0.06% and 1.1%), 1,22‐24 and with that recently reported in a large group of dogs with signs of CGD 16 . However, the results of this study demonstrated a lower prevalence of EEH than previously described in dogs with signs of CGD presented to several referral centers in Germany and in the Netherlands 15 .…”
Section: Discussionsupporting
confidence: 91%
“…15 In the latter study, 6 of the 151 (4%) dogs with signs of CGD were diagnosed with HA and none of these dogs had abnormalities in serum electrolyte concentrations. 15 Unfortunately, as in many other studies, 5,15,16,26 eACTH was not measured which might have led to an overestimation of the true prevalence of EEH. Moreover, it remains unknown whether those cases suffered from primary HA or if some of them might have had secondary HA.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…From a clinical perspective, the consequences of a false positive result are acceptable, as the confirmatory testing is noninvasive and cost effective. In contrast, recent studies have demonstrated that as a screening test, even when used in a population with higher pretest probability, the baseline cortisol test is associated with a higher false positive rate 1,15 . The MLM might therefore be used not only to automatically screen patients for HA, but also refine test selection and save money in HA suspects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies have demonstrated that as a screening test, even when used in a population with higher pretest probability, the baseline cortisol test is associated with a higher false positive rate. 1,15 The MLM might therefore be used not…”
Section: Discussionmentioning
confidence: 99%